A Method of Electroless Silver Plating on the Surface of PA6 Fiber - CHEN Ming (Cailiao Baohu, 2021)
In order to improve the conductive function of PA6 fiber and make it a flexible material with anti electromagnetic shielding, after two step sensitization and silver ammonia solution activation pretreatment, a layer of metallic silver was uniformly deposited on the surface of PA6 fiber fabric by electroless plating to prepare the Ag/PA6 composite.The morphology, element content, adhesion, resistance value and electromagnetic shielding effect of the coating were tested by SEM, EDS, resistance meter and 2G signal of mobile phone.Results showed that the coating was uniform and dense; the content of silver was high, reaching 100%; the adhesion of the coating was good; the resistance per unit length was low, less than 1 Ω, indicating it has good conductivity; 2G signal attenuation of mobile phone reached 50%, which had good anti electromagnetic shielding effect.The technological conditions of electroless plating were as follows: silver nitrate 11 g/L, ammonia water and sodium hydroxide in proper amount ratio were used to prepare 1.1% silver ammonia solution.The components of reducing agent were glucose 10 g/L, tartaric acid 2 g/L, ethanol 100 ml/L.pH value was adjusted to 11～13 by adding 10 g/L sodium hydroxide solution, the temperature was 20～30 ℃, and the reaction time was 3 min.